2021
DOI: 10.1073/pnas.2103020118
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of lysosome-related organelles in color-changing spiders supports intracellular turnover of pigments

Abstract: Pigment organelles of vertebrates belong to the lysosome-related organelle (LRO) family, of which melanin-producing melanosomes are the prototypes. While their anabolism has been extensively unraveled through the study of melanosomes in skin melanocytes, their catabolism remains poorly known. Here, we tap into the unique ability of crab spiders to reversibly change body coloration to examine the catabolism of their pigment organelles. By combining ultrastructural and metal analyses on high-pressure frozen inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…S13 and S16 ). These findings suggest that the two Trp metabolites are likely involved in Zn binding in microenvironments of variable pH and metal ion content, which may arise during the maturation and turnover of the Zn storage granule ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…S13 and S16 ). These findings suggest that the two Trp metabolites are likely involved in Zn binding in microenvironments of variable pH and metal ion content, which may arise during the maturation and turnover of the Zn storage granule ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in fast continuous scanning, data acquisition 1 4 , and the high flux obtained at modern synchrotron-based hard X-ray nanoprobes have opened routine access to scanning 2D multimodal imaging. Amongst the scanning techniques, the high analytical sensitivity of X-ray Fluorescence (XRF) imaging provides unique possibilities in several scientific fields to study the role and fate of trace elements 5 13 . However, the unambiguous interpretation of 2D elemental distribution maps is not always straightforward or feasible and is especially problematic in the case of thick, complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…Bagnara et al, postulated that all vertebrate pigment organelles ('-somes') derive from a common 'primordial vesicle' 21 , originating from the endosomal pathway 19 . Furthermore, it was shown that many of these pigment granules are lysosome-related organelles (LRO) [22][23][24] . Despite their inclusion in .…”
Section: Introductionmentioning
confidence: 99%
“…Bagnara et al, postulated that all vertebrate pigment organelles ('-somes') derive from a common 'primordial vesicle' 21 , originating from the endosomal pathway 19 . Furthermore, it was shown that many of these pigment granules are lysosome-related organelles (LRO) [22][23][24] . Despite their inclusion in the LRO family, iridosomes differ from other pigments in that they generate structural colors from crystals, rather than absorptive colors from pigments.…”
Section: Introductionmentioning
confidence: 99%